(untitled) (Contemporary Journal of Social Science Review, 2025)
Urdu fiction has now been around one hundred and seventeen years old. The journey that Urdu fiction has taken during this time has been identified in the article under consideration. There were three prominent trends in the beginning of Urdu fiction. Rashid Ul-Khairi was the pioneer of reformism, Prem Chand, realism and Sajjad Haider Yeldirim was the pioneer of romanticism. These three streams of Urdu fiction seem to us to be side by side with each other, intersect with each other and merge into each other throughout the journey. They show us their reflection in different proportions in most of the Urdu fiction writers and why not stop at Urdu fiction. These three elements make their presence known in all Urdu literature. This paper focused on the descriptive narrative in the short stories of Sajjad Haider Yeldirim, Prem Chand, Krishan Chander as well.